Conceptual interpretation of myth nature within Ya. E. Golosovker "imaginative absolute" theory - M. V. Sboychikova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Conceptual interpretation and philosophical reflection of myth nature within the "imaginative absolute" theory by Ya. E. Golosovker is of current importance due to the fact that it allows identifying such concepts as "moral", "culture", "god", "religion", so it actually represents a next phase of culture development. The aim of the study is the conceptual interpretation of myth within Ya. E. Golosovker theory and interpretation of overall worldview within this theory. The results: The author has stated and analyzed the main theses of Ya. A. Golosovker theory. Within the theory the meanings of the "culture", "morals", "god", "myth", "religion", "higher instinct", "conscience", "imagination" concepts were displayed. The author makes a conclusion on the origin and function of myth within the "imaginative absolute" theory. The attempt to highlight the overall worldview and meaning of life within the theory was made. The conclusion was made that the world is reasonable Space where the mind plays the role of God and represents supreme value. The superior form of mind, source of culture, meaning and aim of culture is antimoral higher human instinct "imaginative absolute".